Effects of heterogeneous land use/cover types on river channel morphology in the Solo River catchment, Eastern Uganda - Barasa, Bernard; Kakembo, Vincent; Mwololo Waema, Tim; Laban, Macopiyo (Geocarto International, 2015)
In the tropics, unmonitored land use/cover types cause significant effects on the narrowing and widening of river channels which affects the integrity of water resources. River channel planform extent was characterised using Landsat images while water and bedload samples were collected and analysed for a period of one year. The results revealed that in 1986 the channel planform covered 3.7sq.km in length than in 2013 where it increased to 4.2sq.km. Wetland (537.1mgl-1) and bushland (186.3mgl-1) cover types had the highest concentration of suspended sediments. Fine-sand (0.25mm), silty-sand (1mm) and silty-clay (0.125mm) bedload particle types dominated the riverbed along the channel from the sampled land use/cover types. The high concentration of sediments, bedload materials, bank-instability, and stream-flow were significant contributors to the narrowing and widening of the channel (P<0.05). Agricultural landuse was the major contributor of channel aggradation (0.8m) and degradation (0.25m) compared to treeplantations, bushlands, forest and wetland cover types.
Keywords: River channel planform; Sediments; Streamflow; Cross-sections